Challenges and barriers of building information modelling (BIM) implementation in construction industry - Nur Farhana, Hamzah (2018)
Building Information Modelling (BIM) is an intelligent model-based process that provides insight for creating and managing building and infrastructure projects faster, more economically and with less environmental impact. It also represents the process of development and use of a computer generated model to simulate the planning, design, construction and operation of a facility. BIM is defined as a modelling technology and associated set of processes to produce, communicate, and analyse building models throughout the entire project's lifecycle. Although there is bound of benefits that gained from the BIM application, the local construction industry still reluctant to deploy the technology in delivery its services. The objectives of the study is to identify the types of challenges from relevant literature review related to BIM, to design the questionnaire on the challenges and barriers during the implementation of BIM and to analyse the effect of challenges to the outcome of BIM. The survey questionnaires were distributed in the construction field, consultant firm and architecture firm within Klang Valley. The method of data collection is by questionnaire and also simple interview. The main conclusion drawn from the study are cost, lack of collaborative work processes and modelling standards and fragmented nature are the most largest challenges and barriers in the implementation of BIM in construction industry.